NEGARA DALAM PERSPEKTIF ISLAM: KAJIAN AYAT-AYAT AL-QUR’AN TENTANG PRINSIP DAN TUJUAN KENEGARAAN: The State from an Islamic Perspective: A Study of Qur’anic Verses on The Principles and Objectives of State Governance - Rudi Iskandar (STAI Ma'had Aly Al-Hikam Malang, 2025)
In the context of modern state governance, Islamic political values provide an ethical framework to strengthen the integrity of government and public policy. This study explores the principles and objectives of the state in the Qur’an and Hadith, supported by interpretations of classical and contemporary scholars. The aim is to identify the principles of governance and the objectives of the state from an Islamic perspective and to examine their relevance to modern administration. The method used is library research with primary sources from Al-Qur’an, Hadith, and Qur’anic interpretation, along with secondary sources from academic literature. The analysis applies a thematic exegesis approach and qualitative interpretation. The findings show that the principles of Islamic governance include trust (Surah al-Nisa’ [4]: 58), justice (al-Ma’idah [5]: 8), consultation (al-Shura [42]: 38), unity (Ali ‘Imran [3]: 103), and freedom of religion (al-Baqarah [2]: 256). The objectives of the state cover public welfare, the establishment of justice, and the development of a moral society. The implication of this study is that it reinforces previous findings on justice and consultation while adding a new perspective by highlighting the integration of human values and universal welfare in modern governance. The limitation lies in its normative-theological approach, which does not address empirical dimensions, so further research is needed to test the application of these principles in contemporary state governance. Di tengah tata kelola negara modern, nilai-nilai politik Islam memberikan kerangka etis untuk memperkuat integritas pemerintahan dan kebijakan publik. Kajian ini mengeksplorasi prinsip dan tujuan kenegaraan dalam Al-Qur’an dan Hadis, didukung penafsiran ulama klasik dan kontemporer. Tujuannya mengidentifikasi prinsip pemerintahan dan tujuan negara dalam perspektif Islam serta relevansinya dengan administrasi modern. Metode yang digunakan adalah studi pustaka dengan sumber primer berupa Al-Qur’an, Hadis, dan tafsir, serta sumber sekunder dari literatur akademik. Analisis dilakukan melalui pendekatan tafsir tematik dan interpretasi kualitatif. Hasil penelitian menunjukkan bahwa prinsip pemerintahan Islam mencakup amanah (Surat al-Nisa’ [4]: 58), keadilan (al-Ma’idah [5]: 8), musyawarah (al-Syura [42]: 38), persatuan (Ali ‘Imran [3]: 103), dan kebebasan beragama (al-Baqarah [2]: 256). Tujuan negara meliputi kesejahteraan publik, tegaknya keadilan, dan terbentuknya masyarakat bermoral. Implikasi penelitian ini adalah memperkuat temuan terdahulu tentang keadilan dan musyawarah, serta menambah perspektif baru yang menekankan integrasi nilai kemanusiaan dan visi kemaslahatan universal. Limitasinya adalah pendekatan normatif-teologis yang belum menyentuh dimensi empiris, sehingga penelitian lanjutan perlu menguji penerapan prinsip-prinsip ini dalam tata kelola negara modern. Kata Kunci : Etika Politik; Negara Islam; Prinsip Pemerintahan; Tafsir Al-Qur’an; Tujuan Negara.